Framework for the development of computational solutions for the support of requirements engineering with a focus on data protection - Silva, Paulo Henrique Da; Benitti, Fabiane; Wangham, Michelle (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Technological growth has allowed the large-scale processing of personal data, sometimes treated for purposes not previously consented with their subjects or without the required protection. Privacy is a crucial topic that has become popular with the entry into force of regulations such as GDPR and LGPD. Research shows that adhering to these regulations is not trivial for companies that develop solutions that treat personal data. This scenario is worsened by the lack of knowledge of software development teams regarding data protection regulations. In this context, the present work aims to support teams in building software requirements adhering to data protection regulations through a workflow-based framework. The workflow analyzes the requirement from various points of view related to data protection, indicating points of improvement for developing the software in question. We developed a practical example to demonstrate the framework’s applicability, analyzing a software requirement. The obtained results are promising.